Accepting change as part of organisational life - Yolandi Slabbert (Communicare)
This article proposes a new concept, co-change-orientated communication (co-COC), which encapsulates the daily social and communication processes of organisational members in making sense of change from a critical strategic communication perspective. Guided by an evolutionary approach to concept development, this article aims to quantitatively measure the pragmatic relevance of identified attributes and antecedents of co-COC to the development of a fully-fledged concept at six high-change South African organisations. An exploratory factor analysis confirmed that co-COC is attributed by meaningful dialogue, employee engagement, collaboration and co-creation, and the encouragement of dissent. It is bottom-up in nature and enabled by the antecedents of organisational agility, leadership agility, a change-able culture and stakeholder engagement. Co-COC further extends theoretical development on the need for change in approaches to communication that support ongoing organisational change and hasve potential to assist communication professionals to recognise the need and pragmatic relevance of contemporary developments in strategic communication. The various antecedents and attributes of co-COC could also provide organisations with guidance on the implementation of changeorientated communication approaches in support of ongoing organisational change.